WHITHER THE ELEMENTARY SCHOOL SCIENCE PROGRAM? - McAnarney, Harry E. (Science Education, 1969)
The article reports on numerous innovations in elementary school science which are concerned with the improvement of teaching through the use of special materials or procedures. There are several time-tested procedures that are of assistance in directing elementary science programs into more productive channels. The K-12 pattern aids in attaining balance among the earth, biological and physical sciences. Schools should adopt programs in which designated areas are studied every second or third, rather than each year.